Analisis Pengaruh Kompetensi Guru dan Motivasi Kerja terhadap Kinerja Guru pada Sekolah Luar Biasa (SLB) Swasta di Kota Bekasi - Andi Muhammad Sadli; Budi Rachmawati (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
The research aims to explain whether competency and motivation variables affect performance significantly in outstanding schools. This type of research uses primary data collection method which is field research which is conducted with direct observations (observations), interviews and using a list of questions (questionnaires). The results of the study showed that partially competence and motivation have a strong and positive effect on performance judging by the results of the analysis of multiple regression coefficients are Y = 0.199 + 0.229 (X1) + 0.778 (X2 ) means if competence and motivation (X1 and X2 = 0) then performance is 0.199 and if competence and motivation (X1 and X2 = 1) performance 0.299X1 and 0.778 X2. Based on the calculation of the coefficient of determination R2 SPSS program is 0.825 correlation analysis determination R2 obtained value Kd = (0.825x0.825= 0.681 or 68.1%) and the rest by 100% - 68.1% = 31.9% is affected by other variables. Based on the partial competency test result t count 1,782 < 2,019 table with a signification value of 0.82 because the probability of significancy is much greater than 0.05 then Ho is accepted and Ha is rejected. This suggests that partially states that competence does not have a positive and significant influence on performance. Based on the results of the partial test of motivation variable states that t count 6,308 > 2,019 t table, with a significance value of 0.000. Since the probability is significantly smaller than 0.05 then Ho is rejected and Ha accepted. This suggests that partially stating motivation has a positive and significant influence on performance. Based on the hypothesis test f obtained a value of 42,754 with df numerator 2 and df denominator 41 then obtained f table of 3.23. Since f counted 42,754 > f table 3.23, Ho was rejected and Ha accepted, meaning there was a significant influence between competence (X1) and motivation (X2) together on performance variables (Y) in Extraordinary School teachers.